Alcohol in health and disease - Agarwal, Dharam P.; Seitz, Helmut K. (Taylor & Francis Group, 2001)
This volume, based on presentations from the symposium on the health effects of alcohol held in Titisee, Germany, examines the physical and psychological consequences of alcohol use and abuse, and considers environmental and ethnic factors that lead to addiction and dependence. Discusses epidemiological studies that show the influence of light to moderate intake of alcoholic beverages on coronary heart disease! Featuring contributions from nearly 60 internationally recognized and respected authors, and over 2900 references for further investigation of the subject, Alcohol in Health and Disease analyzes biochemical, pharmacogenetic, and pathologic disturbances that follow acute and chronic ingestion of alcohol describes complications that arise from social, biological, and environmental factors examines alcohol metabolic genes and their role in alcohol sensitivity, drinking habits, and dependence spotlights hepatic and nutritional disorders associated with alcoholism considers the relationship of alcohol to cancer debates the French paradox and more! Covering a multitude of disciplines, including molecular biochemistry, genetics, epidemiology, pathophysiology, neurobiology, and cardiology, Alcohol in Health and Disease is a critical reference for addiction psychiatrists, neuropsychopharmacologists, psychologists, geneticists, toxicologists, biochemists, environmental and public health scientists, health policy makers, social workers, counselors, and graduate and medical school students in these disciplines.